Integrative Dimensional Personality Inventory for ICD-11: Development and Evaluation in the Peruvian Correctional Setting - Hualparuca-Olivera, Luis Miguel (2022)
Background: Personality disorder (PD) is an important predictor of the commission of crimes; however, there is a lack of clinical instruments adjusted to the characteristics of Peruvian convicts. Objective: To develop a reliable and valid comprehensive personality measurement instrument, the Integrative Dimensional Personality Inventory, ICD-11 version (IDPI-11), according to the standards of the International Classification of Diseases (ICD-11). Method: A stratified sample of prisoners from the Huancayo Penitentiary (HP) was selected (n study 1 = 60; n study 2 = 1095). Results: High reliability indices (McDonald’s ω ≥ .73) and adequate levels of content validity (CVI-S ≥ .87), construct validity, and criterion validity of the scales were found. This could explain the probability (a) of belonging to the group of inmates with instrumental or impulsive crimes (R2 N ≥ .52, OR ≥ 1.02, p ≤ .021), and (b) that recidivism, designated by the prison security level imposed, increases (R2 ≥ .53, β ≥ 1.16, p ≤ .008). Conclusions: The instrument is a valid and reliable measure that allows a dimensional and integrative assessment of the personality of convicts of the HP, according to ICD-11 standards.  Authors’ contributions LMHO, DNRC, and RMCA conceived the article; DNRC and PAAV collected the data; LMHO and PAAV performed the statistical analysis; LMHO reviewed the contents; and RMCA advised on the entire study and manuscript preparation process.